Benign Mature Cystic Teratoma Masquerading as Recurrent Pneumonia in a Young Adult. - Azhar AH,; Ziyadi G,; Rashidi A,; Rahman MNG, (Department of Surgery, UKM Medical Centre, 2012)
Mediastinal mature cycstic teratomas are rare germ cell tumors most commonly found in the anterior mediastinum, and constitute about 3-12% of all mediastinal tumors. They grow slowly and are usually diagnosed incidentally. This is a rare presentation of a young lady with mediastinal mature cystic teratoma (dermoid cyst) presenting with chronic cough and haemoptysis.